Implementation od preventive measures for reducing the fire risks in UHMC ,,Dr Dragisa Misovic - Dedinje" (International Journal of Contemporary Security Studies, 2024)
Fire have a great potential to threaten people's lives, property, material goods, and the environment, and turn into disasters. The danger of fire, i.e. the risk to people and property, increases especially in public buildings, in which, as a rule, a large number of people are staying at the same time.Numerous experiences have shown that a large number of fires could have been prevented or extinguished at the initial stage, by observing and applying basic fire protection measures. Еarlier approach to fire protection was based on measures aimed to suppress the fire and reduce its consequences, when the fire had already started. The contemporary concept of fire risk reduction involves planning and implementing a series of preventive measures. Preventive measures are the only effective and economical way to protect against fire, and they affect both the prevention of fire occurrence and the significant reduction of negative effects, if a fire occur.
Keywords: objects of public importance, fire, risk reduction, preventive protection measures, fire protection